2016
DOI: 10.1149/2.0891607jes
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hyper-Dendritic Zinc during High Rate Discharge in Alkaline Electrolytes

Abstract: Zinc is a low cost and abundant material, and its strong reducing potential combined with stability in aqueous solutions give it high energy density and safety. It is, therefore, known to be an excellent choice of anode for a wide range of battery designs. However, this material presents some challenges for use in a secondary battery, including morphology changes and dendrite growth during charge (Zn deposition), and low utilization during discharge (Zn dissolution). Low utilization is related to a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…[111] In addition, the rapid corrosion of the Zn anode that leads to the apparent shape change also aggravates dendrite formation. [112,113] These alkaline Zn dendrites show a 1D ramified cone-like topology, which is likely to easily pierce the separators (Figure 5a,b). [34] They can form even under moderate conditions of low capacity and current density, implying that their origin lies in thermodynamic instability.…”
Section: mentioning
confidence: 99%
“…[111] In addition, the rapid corrosion of the Zn anode that leads to the apparent shape change also aggravates dendrite formation. [112,113] These alkaline Zn dendrites show a 1D ramified cone-like topology, which is likely to easily pierce the separators (Figure 5a,b). [34] They can form even under moderate conditions of low capacity and current density, implying that their origin lies in thermodynamic instability.…”
Section: mentioning
confidence: 99%
“…Electrolyte additives in platting solution are considered a promising approach to control parasitic side reactions on Zn‐metal anode and the dendrite suppression. [ 78–80 ] The effect of organic and inorganic additives of Triton X‐100, sodium lauryl sulfate, and Pb 2+ to suppress Zn dendrite in Zn‐polyaniline batteries made with Zn‐metal anode is reported by Kan et al [ 81 ] They have shown that the presence of additives results in smooth and uniform Zn deposition. Tetra‐alkyl ammonium hydroxides are also shown to suppress Zn dendrite in Zn−Ni batteries.…”
Section: Strategies To Suppress Zn Dendrite and Parasitic Side Reactionsmentioning
confidence: 99%
“…Among the above-mentioned RAMBs, those with zinc as the anode material have gained much interest due to the vast availability, low cost, nontoxicity, acceptable volumetric energy density, chemical affinity with aqueous electrolytes, and outstanding electrochemical properties of zinc. These properties suggest that zinc is an ideal negative electrode material for RAMBs. , Furthermore, because zinc is inexpensive and highly reliable, RAMBs with zinc anodes are promising candidates for large-scale ESDs . Much research has been done to utilize several electrode materials as divalent zinc storage hubs. However, RAMBs with superior electrodes that have high capacity, high voltage, and stable electrochemistry and employ zinc as the anode are still under investigation.…”
mentioning
confidence: 99%